2020
DOI: 10.3390/w13010073
|View full text |Cite
|
Sign up to set email alerts
|

Indicative Lake Water Quality Assessment Using Remote Sensing Images-Effect of COVID-19 Lockdown

Abstract: The major lockdown due to the COVID-19 pandemic has affected the socio-economic development of the world. On the other hand, there are also reports of reduced pollution levels. In this study, an indicative analysis is adopted to understand the effect of lockdown on the changes in the water quality parameters for Lake Hussain Sagar using two remote sensing techniques: (i) spectral reflectance (SR) and (ii) chromaticity analysis (Forel-Ule color Index (FUI) and Excitation Purity). The empirical relationships fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 64 publications
(102 reference statements)
0
13
0
Order By: Relevance
“…Similarly, Pinder et al [37] reported that heavily polluted rivers in India have improved substantially with clean clear waters for the first time in decades. Using remote sending techniques in their study of an Indian lake, Wagh et al [38] noted a significant reduction in chlorophyll a, colored dissolved organic matter, and total suspended solids due low pollution discharges during the COVID-19 lockdown period when anthropogenic activities were restricted, and many large and small scaled industries were closed. In addition, Sun et al [4] also noted that turbidity levels in Wuhan lakes significantly decreased due to the sharp reduction in human activities after the lockdown.…”
Section: Positive Impacts Of Covid-19mentioning
confidence: 99%
“…Similarly, Pinder et al [37] reported that heavily polluted rivers in India have improved substantially with clean clear waters for the first time in decades. Using remote sending techniques in their study of an Indian lake, Wagh et al [38] noted a significant reduction in chlorophyll a, colored dissolved organic matter, and total suspended solids due low pollution discharges during the COVID-19 lockdown period when anthropogenic activities were restricted, and many large and small scaled industries were closed. In addition, Sun et al [4] also noted that turbidity levels in Wuhan lakes significantly decreased due to the sharp reduction in human activities after the lockdown.…”
Section: Positive Impacts Of Covid-19mentioning
confidence: 99%
“…Since the reduction of tourists, water quality along beaches in Acapulco (Mexico), Barcelona (Spain), and Salinas (Ecuador) improved noticeably ( Ormaza-Gonzaìlez et al, 2021 ; Zambrano-Monserrate et al, 2020 ). Wagh found a significant reduction in lake water pollution due to lockdown in Lake Hussain Sagar (India) by using two techniques: spectral reflectance and chromaticity analysis ( Wagh et al, 2021 ). The study also observed that pollution concentration levels in the lake were more uniformly distributed during the lockdown, as compared to before lockdown, after the lockdown was lifted (2020) or previous years (2015–2019).…”
Section: Resultsmentioning
confidence: 99%
“…The study also observed that pollution concentration levels in the lake were more uniformly distributed during the lockdown, as compared to before lockdown, after the lockdown was lifted (2020) or previous years (2015–2019). This suggests that the lake pollutant concentration was uniformly distributed on the lake surface due to low effluent influx during the lockdown ( Wagh et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…After the SARS-CoV-2 virus quickly spread across the globe, this problem has received much attention from several authors in the worst-affected countries such as India, Spain, and Italy. To understand the effects of COVID-19 lockdown, Wagh et al (2021) assessed the indicative lake water quality for the Lake Hussain Sagar (India) using Landsat-8 sensor Operational Land Imager (OLI). This study results have shown that there were a reduction in Chlorophyll-a (Chl-a) and Colored Dissolved Organic Matter (CDOM) concentrations and a significant reduction in lake water pollution (Wagh et al 2021).…”
Section: Studies Of Impacts On Water Qualitymentioning
confidence: 99%
“…To understand the effects of COVID-19 lockdown, Wagh et al (2021) assessed the indicative lake water quality for the Lake Hussain Sagar (India) using Landsat-8 sensor Operational Land Imager (OLI). This study results have shown that there were a reduction in Chlorophyll-a (Chl-a) and Colored Dissolved Organic Matter (CDOM) concentrations and a significant reduction in lake water pollution (Wagh et al 2021). From the above discussion, it can be concluded that there has been an improvement in the water quality during the COVID-19 lockdown.…”
Section: Studies Of Impacts On Water Qualitymentioning
confidence: 99%